Critical Analysis of Pathya in Pandu Roga (AYUSHDHARA, 2023)
Desire of life is the most important one to lead qualitative life. To fulfil this desire a healthy diet and regimen or lifestyle should be followed. Wholesome (Pathya) and unwholesome (Apathya) diet plays an important role to maintain health of healthy individual as well in treatment field to get relief from the diseased state. Ayurveda emphasizes upon the concept of Pathya-apathya along with medicine to complete the treatment procedure. Panduroga (anaemia) is a clinical condition represented with the reduction of haemoglobin concentration of blood according to the age, sex, and physiological condition of an individual. In developing countries, it becomes a global problem. In India more than 50% among the vulnerable groups such as pregnant women, infants, young children and adolescents are suffering from anaemia. Government of India has launched different types of programs, like National Nutritional Anaemia Control Program, National Iron Plus Initiative for Anaemia Control program, ICDS etc in different time according to prevalence of anaemia as a preventive measure. To reduce the prevalence of anaemia government has launched POSHANA ABHIYAN in march 2018 to make ANAEMIA MUKTA BHARAT. Prevention and control of anaemia is one of the key strategies of health sector which can be fulfilled by following different guidelines and comprehensive actions in terms of Pathya. Therefore, in this article we are trying to draw a concept of Pathya in relation to Pandu (haemoglobin level- below the 10gm/dl and above 7gm/dl, through diet and regimen) which may helpful to eradicate prevalence of IDA.